2020
DOI: 10.4171/jncg/391
|View full text |Cite
|
Sign up to set email alerts
|

The relative Mishchenko–Fomenko higher index and almost flat bundles. I. The relative Mishchenko–Fomenko index

Abstract: In this paper, the first of two, we introduce an alternative definition of the Chang–Weinberger–Yu relative higher index, which is thought of as a relative analogue of the Mishchenko–Fomenko index pairing. A main result of this paper is that our map coincides with the existing relative higher index maps. We make use of this fact for understanding the relative higher index. First, we relate the relative higher index with the higher index of the corresponding amalgamated free product group. Second, we define the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…)) is injective. We mention that Y. Kubota also proved the above maximal strong relative Novikov conjecture under slightly stronger assumptions [15]. We thank Y. Kubota for bringing this to our attention.…”
Section: Introductionmentioning
confidence: 72%
“…)) is injective. We mention that Y. Kubota also proved the above maximal strong relative Novikov conjecture under slightly stronger assumptions [15]. We thank Y. Kubota for bringing this to our attention.…”
Section: Introductionmentioning
confidence: 72%
“…However, they could not show in full generality that their relative index map coincides with that of Chang, Weinberger and Yu. In [19], Kubota gave a definition of the relative index map as a relative Mischenko-Fomenko index pairing and showed that it coincides with both that of Chang, Weinberger and Yu and Deeley and Goffeng. Using his work, one can show that the main theorem of Chapter 2 is actually equivalent to the result of Deeley and Goffeng mentioned above.…”
Section: Overview and Outlookmentioning
confidence: 82%
“…Indeed, in [4] it is not even proved in general that the constructions coincide with the ones of [2]. Yet another approach to relative index theory and the results of [2] is given by Kubota in [19]. There, the new concepts of relative Mishchenko bundles and Mishchenko-Fomenko index theory are introduced, and heavy use is made of the machinery of KKtheory.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations